Novel archetypes of new coupled Konno-Oono equation by using sine-Gordon expansion method - Yel, Gulnur; Baskonus, Haci Mehmet; Bulut, Hasan (Springer, 2017)
In this manuscript, we investigate the analytical solutions of the new coupled Konno-Oono equation by using the sine-Gordon expansion method. We successfully obtained some new soliton solutions to this model. We plot the 2D and 3D surfaces of all the found soliton solutions in this study. The Wolfram Mathematica 9 is used in performing all the computations in this study.
Keywords: The sine-Gordon expansion method; The new coupled Konno-Oono equation; Complex hyperbolic solutions